Can mentoring promote self-esteem and school connectedness? An evaluation of the Mentor-UP project - Marino, Claudia, (Colegio Oficial de Psicólogos de Madrid, 2020)
Research in the United States has shown that youth mentoring is a promising strategy for increasing self-esteem and school connectedness in at-risk youth. There has been little confirmation of those findings internationally. The current study evaluates the impact of mentoring by trained university students on childrens self-esteem and school connectedness compared to schoolmates not involved in the program. Mentor-UP is a school- and community-based weekly mentoring program implemented in northern Italy over a period of seven months. Participants (209 students - 34 in the experimental group and 175 in the comparison group - aged between 11 and 13, 56% male, 27% immigrants) reported their levels of self- esteem and school connectedness at the beginning and at the end of the program. Results showed a significant increase in mentees self-esteem compared to the control group, while the difference in school-connectedness was nonsignificant. The findings support the effectiveness of Mentor-UP in nurturing youths self-esteem.